The models of distance forms of learning in National academy of statistics, accounting and audit - Deryhlazov, L. V.; Kukharenko, V. M.; Perkhun, L. P.; Tovmachenko, N. M. (My University, 2017)
Finding solutions to the problems faced by the Ukrainian education system require an adequate organizing structure for education system, enabling transition to the principle of a "life-long education". The best option for this is the distance learning systems (DLS), which are considered by leading Ukrainian universities as high-performance information technologies in modern education, envisaged by the National Informatization Program, with the goals of reforming higher education in Ukraine in the context of joining the European educational space.The article analyzes and summarizes the experience of implementing DLS "Prometheus" and Moodle and the main directions of distance learning development at the National Academy of Statistics, Accounting and Auditing (NASAA). The emphasis is on the need to improve the skills of teachers with the use of open distance courses and the gradual preparation of the student for a learning process in the new conditions. The structure of distance courses for different forms of education (full-time, part-time, mixed) has been developed. The analysis models of forms of learning (Face to face, the driver complementary, rotation model; flex model, etc.) is presented. Dynamic version of the implementation of mixed learning models of NASAA using DLS "Prometheus" and Moodle is presented. The conclusion is that the experience of NASAA shows that the mixed form of distance learning based on Moodle platform is most adequate to the requirements of Ukraine's development within the framework of European education.
Keywords: distance learning; mixed learning; life-long education; information technologies; distance learning courses; distance learning system; learning management system; "Prometheus"; "Moodle"